O conceito de intencionalidade na Quinta Investigação de Edmund Husserl (1859-1938) - Brandes, Lucíola Maria de Sousa (2017)
The present work tries to interpret the concept of intentionality treated in the Fifth Investigation of the work Logical Investigations, of Edmund Husserl (1859-1938). In order to do so, it aims at three objectives: to show that intentionality is not an external relation; prove that intentionality does not presuppose the existence of two different entities; and explicit aspects necessary for the occurrence of intentionality. The development of this study is organized in three chapters. The first takes care of the conception of intentionality in Franz Brentano (1838-1917) and Kasimir Twardowski (1866-1938). In this section, questions about the structure of psychic phenomena and their classification are contemplated, including the characteristics of the representation, the represented object and the content. The second, which constitutes the core of the dissertation, exposes Husserl's concept of intentionality, elaborated in the Fifth Research, based on the central conceptual analyzes and distinctions of this author. This chapter clarifies the structure of intentional living; displays the classification of acts and their fundamental relationships; and provides the four senses of representation. The third examines Husserl's criticisms of Brentano and Twardowski's conceptions of intentional phenomena. The result of this philosophical study indicates that: intentionality, according to Husserl, is based on an inner moment of the experience itself. Husserl distinguishes consciousness from actual objects and representations of fantasy, predictions, memories, and so on; and the object intentionally visualized is neither part of consciousness and is not contained in it, i.e. intentionality is characterized by its independence from existence